2023
DOI: 10.1007/s42250-023-00633-3
|View full text |Cite
|
Sign up to set email alerts
|

A Multidimensional Review of Pimpinella anisum and Recommendation for Future Research to Face Adverse Climatic Conditions

Abstract: Anise, or Pimpinella anisum , has a long history of usage in traditional and alternative medicine, as well as in the pharmaceutical sector . The species is native to Southwest Asia, the Middle East, and the Mediterranean region. The current studies have revealed that wild and cultivated P. anisum are rich in bioactive compounds, such as phenols, tannins, carotenoids, and fatty acids. Different parts of P. anisum plant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 103 publications
0
3
0
Order By: Relevance
“…A. millefolium is native to temperate regions (Vélez-Gavilán, 2016) and T. pulegioides is a herb specialised to semi-natural grassland growing on infertile soils throughout Asia, North Africa and Europe (Vanden Broeck et al, 2015). P. anisum is native to the Mediterranean region and is cultivated in Asia and the Middle East (Soussi et al, 2023). P. saxifraga is used across Europe and is adapted to old calcareous grassland on infertile soil (Grime et al, 1988) that is managed under infrequent defoliation without fertilisation (Auestad et al, 2010).…”
Section: Chosen Plant Speciesmentioning
confidence: 99%
“…A. millefolium is native to temperate regions (Vélez-Gavilán, 2016) and T. pulegioides is a herb specialised to semi-natural grassland growing on infertile soils throughout Asia, North Africa and Europe (Vanden Broeck et al, 2015). P. anisum is native to the Mediterranean region and is cultivated in Asia and the Middle East (Soussi et al, 2023). P. saxifraga is used across Europe and is adapted to old calcareous grassland on infertile soil (Grime et al, 1988) that is managed under infrequent defoliation without fertilisation (Auestad et al, 2010).…”
Section: Chosen Plant Speciesmentioning
confidence: 99%
“…Recent research has demonstrated that anise seeds have antiviral, antifungal, antibacterial, anti-inflammatory, anticonvulsant, analgesic, and anti-diabetic properties (Sun et al 2019;Ghosh et al 2019;El-Rokiek et al 2020). These activities are offered by the diversity and quantity of chemical compounds recorded in this plant's essential oils and extracts (Sun et al 2019;Soussi et al 2022Soussi et al , 2023. For example, Anise is rich in anethole, used in the food, pharmaceutical, flavoring, and perfumery industry (Özcan and Chalchat 2006;Tuncturk and Yildirim 2011).…”
Section: Therapeutic Uses Of Anise Seedmentioning
confidence: 99%
“…The perfume and flavour of anise are attributed to its well-known essential oil. Despite transanethole making up between 75 and 90 percent of anise oil, there are other components including coumarins (umbelliprenine, umbelliferone, bergapten, and scopoletin), flavonoids (flavonol, glycosides, isoorientin, flavone, rutin, and isovitexin), lipids (betaarmyrin, stigmasterol, fatty acids, and its salts), carbohydrates, and proteins (Picon et al 2010;Sun et al 2019;Soussi et al 2023). These compounds are behind the therapeutic and food benefits of anise.…”
Section: Introductionmentioning
confidence: 99%